Late preterm and early term: when to induce a growth restricted fetus? A population-based study†. (3rd April 2018) - Rabinovich, Alex; Tsemach, Tehila; Novack, Lena; Mazor, Moshe; Rafaeli-Yehudai, Tal; Staretz-Chacham, Orna; Beer-Weisel, Ruth; Klaitman-Mayer, Vered; Mastrolia, Salvatore A; Erez, Offer
Abstract: Purpose: (1) Compare fetal and neonatal morbidity and mortality associated with induction of labor (IOL) versus expectant management (EM) in women with isolated fetal growth restriction (FGR) between 34 0/7 and 38 6/7 weeks; (2) Determine optimal gestational age for delivery of such fetuses. Materials and methods: A retrospective population based cohort study of 2232 parturients with isolated FGR, including two groups: (1) IOL ( n  = 1428); 2) EM ( n  = 804). Results: IOL group had a lower stillbirth and neonatal death rates ( p  = .042, p  < .001), higher 1 and 5 min Apgar scores and a higher vaginal delivery rate compared to the EM group. In the late preterm period, EM was associated with increased rate of low 1 and 5 min Apgar scores, nonreassuring fetal heart rate tracing (NRFHR), stillbirth and neonatal death rate ( p  = .001, p  = .039). In the early term cohort, EM was associated with a higher rate of NRFHR and low 1 min Apgar scores ( p  = .003, p  = .002). IOL at 37 weeks protected from stillbirth but not from adverse composite neonatal outcomes. Conclusions: IOL of FGR fetuses at 37 weeks had a protective effect against stillbirth. In addition, at late preterm, it is associated with lower rates of stillbirth, neonatal death, and NRFHR.